Biological Nitrogen Fixation and Nitrogen Accumulation in Peatlands - Yin, Tianya; Feng, Maoyuan; Qiu, Chunjing; Peng, Shushi (Frontiers in Earth Science, 2022)
Peatlands cover about 3% of the Earth’s surface and are regarded as a vital carbon (C) pool and sink. The formation of peatland is supported by continuously supplied nitrogen (N) but the sources of this N remain unclear. Here, we first review N stocks and the rate they accumulate in peatlands, then we present the sources of N, especially through biological nitrogen fixation (BNF). We found that global peatlands store 5.9–25.9 Gt N. In the past millennia, northern peatlands have a lower N accumulated rate than tropical undisturbed peatlands. BNF rate is approximately 1.9±2.7 g m-2 yr-1 in northern peatlands, higher than the rate of N deposition, 0.5±0.4 g m-2 yr-1. For tropical peatlands, BNF observation has hardly been reported yet and needs further investigation. This review provides a broad picture of peatland N cycling and suggests that there are large uncertainties, due to limited observations of BNF and N fluxes by inflow and outflow runoff. Therefore, we call for more efforts contributing to field observations and modelling of the N budget in peatlands.